A Nationwide Study of ADHD Drug Use among Adults in Iceland 2003-2012 - Drífa Pálín Geirsdóttir 1978- (2014)
In this study we leveraged on complete nationwide prescription data for the total adult population in Iceland (N=227,000), to examine how attention-deficit/hyperactivity disorder (ADHD) drugs have been used over the past decade. In particular we aimed to describe the prevalence, incidence and duration of use of stimulants and atomoxetine, among adults (≥19 years) in Iceland, with regard to sex, age, type of drug and specialty of the prescribing physician. Our results indicate that the 1-year period prevalence of ADHD drug use rose, from 2.9 to 12.2 per 1,000 adults between 2003 and 2012, with the most pronounced increases among young adults (19-24 years). The annual incidence increased 3-fold, similarly among men and women. Extended release methylphenidate formulations were the most commonly used ADHD drugs. Specialists in psychiatry initiated treatment in 79% of new adult ADHD drug users. The proportion of users still receiving treatment after one year varied from 43.0% (19-24 years), 57.2% (25-49 years) to 47.5% (50+ years). After 3 years, the corresponding proportions still on treatment were 12.4%, 24.5% and 24.3%, and after 5 years 7.9%, 15.9% and 16.8%. These results of increasing ADHD drug use and short treatment durations call for further investigation of the quality of treatment regimens for adults with ADHD and better follow-up of patients treated with ADHD drugs. Keywords: attention deficit/ hyperactivity disorder; ADHD; pharmacoepidemiology; drug utilization; treatment duration; central nervous system stimulants; adults Rannsóknir sýna að 50% einstaklinga sem greindir eru með einkenni athyglisbrests með ofvirkni (Attention Deficit Hyperactivity Disorder; ADHD) í æsku hafa enn einkenni á fullorðinsárum. Rannsóknir sem gerðar hafa verið á umfangi og þróun notkunar ADHD lyfja á Íslandi hafa fyrst og fremst snúið að börnum. Engin heildstæð úttekt hefur verið gerð á ADHD lyfjanotkun hjá fullorðnum einstaklingum á Íslandi. Markmið þessarar rannsóknar var að lýsa algengi og nýgengi ADHD lyfjanotkunar sem ...